Association of sleep duration and sleep quality with overweight/obesity among adolescents of Bangladesh: a multilevel analysis - Md Rifat Anam; Shamima Akter; Fahima Hossain; Sharmin Quazi Bonny; Jahanara Akter; Cherri Zhang; Md. Mizanur Rahman; Md. Abul Basher Mian (BMC, 2022)
Abstract Background Sleep deprivation is widely recognized as a potential contributor to childhood obesity. However, few studies have addressed this issue in low-income settings. The aim of this study was to determine the association of both sleep duration and sleep quality with overweight/obesity among adolescents of Bangladesh. Methods A cross-sectional study was conducted in four randomly selected schools in Gazipur, Bangladesh, from May to August 2019. Using a self-administered semi-structured questionnaire, data on sleep duration and sleep quality were collected from 1,044 adolescents between 13 and 17 years of age. The body mass indices of the study participants were evaluated using their objectively-assessed anthropometric measurements (weight and height). Multilevel logistic regression was used for data analysis. Results The prevalence of underweight, overweight and obesity in adolescents in this study were 14.9, 18 and 7.1%, respectively. More than 15% of the students reported sleep disturbance and poor sleep quality. After adjusting for confounders, reduced (<7 h/day) total sleep duration (OR=1.73, 95% CI=1.21-2.47), weekend sleep duration (OR=1.46, 95% CI=1.00-2.12), and night sleep duration (OR=1.55, 95% CI=1.06-2.28) were found to be significantly associated with overweight or obesity in Bangladeshi adolescents. Similarly, significant positive associations were evident between short duration of total sleep (OR=0.33, 95% CI=0.20-0.54), weekday sleep (OR=0.55, 95% CI=0.35-0.84), weekend sleep (OR=0.53, 95% CI=0.31-0.89), and night sleep (OR=0.56, 95% CI=0.36-0.87), and underweight in study participants. Adolescents with short sleep duration were found less likely to be underweight and more likely to be overweight/obese. Conclusions Study findings denoted short sleep duration to be associated with overweight/obesity and underweight among adolescents of Bangladesh. Adequate sleep may therefore serve as an effective obesity prevention strategy in the growing stages.